Individuals With Pre-arthritic Hip Pain Walk With Hip Motion Alterations Common in Individuals With Hip OA - Cara L. Lewis; Anne L. Halverstadt; Kerri A. Graber; Zoe Perkins; Emily Keiser; Hadwin Belcher; Anne Khuu; Kari L. Loverro; Kari L. Loverro (Frontiers Media S.A., 2021)
Background: Individuals with hip osteoarthritis (OA) commonly walk with less hip extension compared to individuals without hip OA. This alteration is often attributed to walking speed, structural limitation, and/or hip pain. It is unclear if individuals who are at increased risk for future OA (i.e., individuals with pre-arthritic hip disease [PAHD]) also walk with decreased hip extension.Objectives: (1) Determine if individuals with PAHD exhibit less hip extension compared to individuals without hip pain during walking, and (2) investigate potential reasons for these motion alterations.Methods: Adolescent and adult individuals with PAHD and healthy controls without hip pain were recruited for the study. Kinematic data were collected while walking on a treadmill at three walking speeds: preferred, fast (25% faster than preferred), and prescribed (1.25 m/s). Peak hip extension, peak hip flexion, and hip excursion were calculated for each speed. Linear regression analyses were used to examine the effects of group, sex, side, and their interactions.Results: Individuals with PAHD had 2.9° less peak hip extension compared to individuals in the Control group (p = 0.014) when walking at their preferred speed. At the prescribed speed, the PAHD group walked with 2.7° less hip extension than the Control group (p = 0.022). Given the persistence of the finding despite walking at the same speed, differences in preferred speed are unlikely the reason for the reduced hip extension. At the fast speed, both groups increased their hip extension, hip flexion, and hip excursion by similar amounts. Hip extension was less in the PAHD group compared to the Control group (p = 0.008) with no significant group-by-task interaction (p = 0.206). Within the PAHD group, hip angles and excursions were similar between individuals reporting pain and individuals reporting no pain.Conclusions: The results of this study indicate that kinematic alterations common in individuals with hip OA exist early in the continuum of hip disease and are present in individuals with PAHD. The reduced hip extension during walking is not explained by speed, structural limitation, or current pain.